ANALISA PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA WAREHOUSE PADA PT HARMONI MITRA UTAMA PALEMBANG - Rusma Rizal (Universitas Indo Global Mandiri)
This study aims to analyze the development of human resources on warehouse performance at PT Harmoni Mitra Utama Palembang. The problem that arises is in the management of PT Harmoni Mitra Utama Palembang's warehouses still do not get the maximum result because it still found the problem of discrepancies such as sending spare parts, passing the quality inspection spare parts process incoming to less accept spare parts or accept damaged spare parts causing loss on the company as well as lead time processes beyond the agreed SLA. The result of the research shows that the warehouse employee performance is not maximally seen in the SLA activity report of 2016 from the standard process agreement level that is determined there are 4 activities that do not meet, among others, incoming and outgoing spare parts, autif activities, and discrepancies with 90% target. To improve the employee's performance, the following steps are defined: a company conducts Employee Selection, conducts Competency Mapping followed by management actions and runs Standard operational procedures that have been made by the company.keywords: kinerja, warehouse, sumber daya manusia.